Czy nastąpiła już dewaluacja uczciwości? - Katarzyna Polus-Rogalska (Świat Idei i Polityki, 2001)
We all reflect on the problem what has happened to the sense of honesty in our country. In the article, apart from presenting the problem, the author suggests precautions that are to be taken to solve this matter. First, it seems to be necessary to reveal the incomes of politicians and to eliminate profits from different kinds of services and hardly measurable privileges (it is suggested that politicians’ salaries should oscillate in range of mean incomes the citizens obtained under their government). Second, moral standards have to be of a prior character. Third, the struggle for raising morality to higher level cannot be single only, but a long and continuous activity that would have to be subordinated to other current affairs And finally, the struggle for moral values ought to join all people, as the effects that result from failing ethics burden our lives and are a plague of ordinariness. The author concludes that if any significant changes do not take place in social systems and in conscious educational actions, the process of value degradation is expected to follow and the whole system of values will be still attacked.